Factors Contributing to Examination Malpractices at Secondary School Level in Kohat Division, Pakistan - Qaiser Suleman; Rizwana Gul; Sadia Ambrin; Farrukh Kamran (Journal of Education and Learning (EduLearn), 2015)
The purpose of this research work was to identify the factors that contribute to examination malpractices at secondary school level. The target population of the study was all the heads, teachers and students at secondary school level in Kohat Division (Pakistan). The study was delimited to the 80 male secondary schools. The sample for this study was made up of 840 respondents which were selected through simple random sampling technique. A self-developed semi-structured questionnaire was used as research instrument for data collection. Descriptive statistics i.e., simple percentage, mean, standard deviation and inferential statistics i.e., ANOVA were applied for the statistical analysis of data. The findings of the study explored that there are various factors that contribute to examination malpractices i.e., corruption; poor implementation of examinations rules; students and parental threats; no fear of punishment; inadequate preparation for examination; poor invigilation; collusion; disloyalty of examination bodies; fear of failure; poor morale and economic depression of supervisory staff etc. Furthermore, the findings of the study revealed that bringing of unauthorized materials to examination hall; sending of prepared answers to students by teachers and parents; impersonation; questions and papers leakage; cheating; and scripts changing are the various forms of examination malpractices. Based on findings, it was recommended that examination rules should be implemented effectively and those who were found guilty should be given severe exemplary punishment according to the examination’s rules.